The Impact of Nutritional Intake on Bilirubin Levels in Hospitalized Neonates with Hyperbilirubinemia - Dwiyanti Purbasari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Newborns commonly experience an increase in bilirubin levels starting from the first day of life. If not properly managed, this condition can develop into hyperbilirubinemia—a frequently encountered health issue among neonates that may lead to severe neurological complications. Nutritional intake, particularly breastfeeding, is believed to play a crucial role in the elimination of bilirubin through feces and urine. Objective: This study aimed to analyze the relationship between nutritional intake and total bilirubin levels in neonates with hyperbilirubinemia on the final day of hospitalization. Methods: This research employed an analytical correlational design with a cross-sectional approach. A total of 34 respondents were selected using accidental sampling during of June at Waled Regional Public Hospital, Cirebon Regency. Data analysis was performed using Pearson’s correlation test. Results: The findings revealed a significant relationship between nutritional intake and total bilirubin levels in neonates with hyperbilirubinemia (p-value = 0.001; r = -0.542), indicating a moderate negative correlation. Conclusion: Adequate nutritional intake, especially breastfeeding, combined with appropriate medical management, plays an important role in reducing bilirubin levels in neonates with hyperbilirubinemia.